INOVASI PEMBELAJARAN PPKN BERBASIS TEKNOLOGI DIGITAL UNTUK MEMBANGUN LITERASI ETIKA DAN TANGGUNG JAWAB DIGITAL SISWA SD DI ERA MEDIA SOSIAL - Dwi Agung Prasetiyo; Erlina Yuliastuti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the development of digital technology-based Pancasila and Citizenship Education (PPKn) learning innovations to help elementary school students develop digital ethics and responsibility in the social media era. The research method used is descriptive qualitative research with a literature review of PPKn learning approaches that integrate digital technology, moral principles, and digital citizenship competencies using literature review techniques. The results of this study indicate that innovations in Pancasila and Citizenship Education (PPKn) learning using digital technology have transformed teaching methods. Teachers can use computers, the internet, and applications to make learning more engaging. Students learn in a collaborative atmosphere through digital media, games, and videos. Technology increases student participation and critical thinking skills. Integrating digital literacy helps students understand ethics, privacy, and responsibility in cyberspace. Projects such as Project Citizen Digital and ethical case simulations improve these skills. However, there are obstacles such as a lack of infrastructure and teacher competency. Collaboration between the government, schools, and parents is needed for this support.